NMR, x-ray, and Mössbauer results for amorphous Li-Si alloys using density functional tight-binding method - Fernandez, Francisco (2023)
Silicon anodes hold great promise for next-generation Li-ion batteries. The main obstacle to exploiting their high performance is the challenge of linking experimental observations to atomic structures due to the amorphous nature of Li-Si alloys. We unveil the atomistic-scale structures of amorphous Li-Si using our recently developed density functional tight-binding model. Our claim is supported by the successful reproduction of experimental x-ray pair distribution functions, NMR, and Mössbauer spectra using simple nearest-neighbor models. The predicted structures are publicly available.